2017
DOI: 10.17957/ijab/15.0284
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementing Olive, Blackseed and Flaxseed Oils on Growth Performance and Serum Biochemistry of Broiler and Economics of its Production

Abstract: This study was conducted to investigate the effect of olive oil, blackseed oil and flaxseed oil on growth performance and serum biochemistry of broiler chicks. Three hundred broiler chicks were grouped into 30 experimental units having 10 chicks each. Three levels (0.5, 1.0 and 1.5%) of each of the oils were offered to the chicks such that each treatment was replicated thrice. The chicks fed on basal diet served as a control. The data on weekly body weight gain, feed intake, weekly feed conversion ratio, Newca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…In agreement with the obtained results in our study, Ashraf et al (2017) found that supplementation of olive oil, black seed oil and flaxseed oil on serum biochemicals of broiler chicks, involving lipid profile (serum cholesterol, triglycerides, HDL and LDL). This reduction may be due to presence of omega 6 fatty acids which have the ability to decrease the cholesterol level in blood serum, while omega 3 fatty acids decrease cholesterol and triglycerides levels (An et al, 1997).…”
Section: Concentration Of Blood Biochemicalsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with the obtained results in our study, Ashraf et al (2017) found that supplementation of olive oil, black seed oil and flaxseed oil on serum biochemicals of broiler chicks, involving lipid profile (serum cholesterol, triglycerides, HDL and LDL). This reduction may be due to presence of omega 6 fatty acids which have the ability to decrease the cholesterol level in blood serum, while omega 3 fatty acids decrease cholesterol and triglycerides levels (An et al, 1997).…”
Section: Concentration Of Blood Biochemicalsupporting
confidence: 93%
“…This may be attributed to that growing rabbits at early age post-weaning required a transit period to adapt on increasing level of dietary fats. The present results agreed with Ashraf et al (2017), who investigated the effect of olive oil, blackseed oil and flaxseed oil on growth performance of broiler chicks. They found that, the heaviest weight was observed in the treatment having flaxseed oil 0.5%, followed by the treatment group having olive oil at levels of 1.0 and 0.5%, respectively.…”
Section: Live Body Weightsupporting
confidence: 93%
See 1 more Smart Citation
“…A recent study by [37] indicated that treatment with BSs and curcumin decreased the risk of exposure to Infectious bursal disease vaccine, improved general health condition and immune status of chicks. With the same line, [57] was observed the highest value of the antibody titer of chicks against ND in the treatment feeding 0.5% BSso.…”
Section: The Effects Of Black Seeds On Immunity and Immune Responsesmentioning
confidence: 55%
“…In agreement with the obtained results of FSO as a source of n-3 fatty acids, Shams (2019) found insignificant effect of dietary olive oil supplementation (0.2, 0.4 and 0.6%) on concentration of total cholesterol, triglycerides, LDL and HDL in blood of growing rabbits. Also, Ashraf et al (2017) found insignificant effect of different dietary sources (olive oil, black seed oil and flaxseed oil) on serum cholesterol, triglycerides and HDL. Moreover, Zibaeenezhad et al (2017) observed that Castelli II index did not change following the feeding on fish oil or fresh fish in human.…”
Section: Lipid Profile In Blood Serummentioning
confidence: 92%